Historical Field Records Reveal Habitat as an Ecological Correlate of Locomotor Phenotypic Diversity in the Radiation of Neotropical Geophagini Fishes - Astudillo-Clavijo, Viviana; Varella, Henrique [UNESP]; Mankis, Tobias; López-Fernández, Hernán (University of Chicago Press, 2024)
Phenotypic macroevolutionary studies provide insight into how ecological processes shape biodiversity. However, the complexity of phenotype-ecology relationships underscores the importance of also validating phenotype-based ecological inference with direct evidence of resource use. Unfortunately, macroevolutionary-scale ecological studies are often hindered by the challenges of acquiring taxonomically and spatially representative ecological data for large and widely distributed clades. The South American cichlid fish tribe Geophagini represents a continentally distributed radiation whose early locomotor morphological divergence suggests habitat as one ecological correlate of diversification, but an association between loco-motor traits and habitat preference has not been corroborated. Field notes accumulated over decades of collecting across South America provide firsthand environmental records that can be mined for habitat data in support of macroevolutionary ecological research. In this study, we applied a newly developed method to transform descriptive field note information into quantitative habitat data and used it to assess habitat preference and its relationship to locomotor morphology in Geophagini. Field note–derived data shed light on geophagine habitat use patterns and reinforced habitat as an ecological correlate of locomotor morphological diversity. Our work emphasizes the rich data potential of museum collections, including often-overlooked material such as field notes, for evolutionary and ecological research.
Keywords: Cichlidae; field notes; Geophagini; habitat; locomotion; Neotropics